Job satisfaction of occupational therapy teachers - Caballero, Marieliz V.
Information on the job satisfaction of faculty members is important in determining whether they are most likely to remain in teaching and what aspects of their performance are believed to be satisfying. Changes of satisfaction between periods of employment to present employment can also be helpful to fully understand and identify factors that can affect quality of performance. Persons who manage faculty members are provided with information on what energizes each member. The administration can do a great deal in understanding individual characteristics of their faculty and reducing demotivating factors which could lead to stress and burnout. This paper aimed to identify levels of satisfaction among full time OT teachers working in the academe from period of recruitment to present employment. Significant differences were also noted based on individual profiles and experiences. Fourteen respondents from schools covering the National Capital Region, Cordillera Administrative Region and Region 3, 4, and 7 participated in the study using purposive sampling. Only full time teachers with academic appointment were chosen for the study. Data were collected using behaviorally anchored rating and key informant interviews to triangulate results and minimize bias. The questionnaire used two-response format with a four-point horizontal Likert scale - which for positive statements, ranged from strongly disagree (1) to strongly agree (2) Negatively phrased statements were reversed (e.g. I feel as though I am in the wrong job) to equalize the outcome of the statement on sum of the score, so that a positive score is achieved. Items adapted from previous studies were used to infer the general job satisfaction of OT faculty and specific tests to measure the following variables: school management, work conditions, relationships with colleagues, and promotional opportunities. It also measured the four dimensions of the job that included professional development, administrative work, research and teaching activities. The respondents gave two answers to each item: (a) the satisfaction that he/she felt in the initial stages of his work/job, and (b) the satisfaction that he or she perceived at present. The results indicated that there is increased dissatisfaction among female, tenured, married faculty members who hold an advanced degree in the areas of school management, work conditions, professional competence, and administrative duties. Teachers with high educational level are more dissatisfied with the intrinsic aspects of teaching such as creating and designing programs for students but believed to have more opportunities for advancement than those who held baccalaureate level. Most of the respondents expressed lack of collegiality among peers that could greatly influence satisfaction in the workplace. Overall job satisfaction was found among male, single and non-tenured faculty members with a minimum work experience of 5 years. Older and more experienced teachers specifically those who are working from 5 years and above were believed to be more prone to financial and psychological changes which when left unnoticed can lead to disillusionment and burnout. Certain aspects of job satisfaction and their effect on quality of performance such as career longevity, characteristics of the faculty and the intrinsic factors involved must be addressed that might positively affect issues concerning recruitment, retention, promotion prospects of OT faculty members in the academia.